Global Studies: Impact on Student-Athlete Engagement and Identity Development in Higher Education. Issue 1 (2nd January 2020) - Navarro, Kristina; Williams, Joshua; Pittelkow, Lily; Schulenberg, Chelsey; Morris, Mario; Salm, Michael J.
Abstract: Drawing on the lived experiences of student-athletes who have participated in global study abroad experiences, researchers sought to specifically understand how to best integrate student-athletes within study abroad programs in American higher education institutions. In turn, the primary objective of this study was to better understand ways in which global experiences influenced student-athletes' engagement and identity development processes. Specifically, this study explored how global study experiences influenced student-athletes' personal, professional; and cultural growth during the higher educational experience. Results demonstrated student-athletes who participated in study abroad opportunities discussed academic, social; and career development benefits that would assist with their development during college and transition to life after sport.